2020
DOI: 10.1177/0003134820943648
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Analysis of Functional Outcomes in Traumatic Brain Injury Patients

Abstract: Introduction Traumatic brain injury (TBI) remains a significant cause of morbidity and mortality. The purpose of this study is to examine outcomes after discharge and identify factors from the index admission that may contribute to long-term mortality. Methods The study population is composed of patients who survived to discharge from a previously published study examining TBI. Demographics, injury severity, and length of stay were abstracted from the index study. Phone surveys of surviving patients were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Our pooled analyses also indicate that β-blockers improved long-term functional outcome in TBI (OR, 1.75; 95% CI, 1.09–2.80; I 2 = 0%; p = 0.02). However, in the index study of 1,615 TBI patients, Schroeppel et al 54 concluded that β-blockers were not predictive of outcomes after discharge. In addition, despite this potential beneficial effect of β-blockers on long-term outcomes, the similar result has not been found at hospital discharge in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our pooled analyses also indicate that β-blockers improved long-term functional outcome in TBI (OR, 1.75; 95% CI, 1.09–2.80; I 2 = 0%; p = 0.02). However, in the index study of 1,615 TBI patients, Schroeppel et al 54 concluded that β-blockers were not predictive of outcomes after discharge. In addition, despite this potential beneficial effect of β-blockers on long-term outcomes, the similar result has not been found at hospital discharge in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term consequences of TBI include increased likelihood of mortality, vegetative status, physical disabilities, cognitive impairment, psychiatric disorders, seizures, and unemployment rate (Stocchetti and Zanier, 2016). Younger age was associated with higher likelihood of survival at follow-up in an adult trauma center patient cohort (Schroeppel et al, 2020). Based on a retrospective study on TBI outcomes in children, it was found that children under 2 years old who experienced TBI were more likely to experience vomiting and post-traumatic epilepsy as the most common symptom (Hwang et al, 2019).…”
Section: Recovery From Tbi and Long-term Outcomesmentioning
confidence: 96%